Long-Lasting Pathological Mental Fatigue After Brain Injury–A Dysfunction in Glutamate Neurotransmission? - Rönnbäck, Lars; Johansson, Birgitta (Frontiers in Behavioral Neuroscience, 2022)
Long-lasting mental or cognitive fatigue may be a disabling symptom after physically recovered skull trauma, stroke, infection or inflammation in the central nervous system (CNS). It is difficult to go back to work and participate in familiar social activities, as typically the person is only able to remain mentally active for short periods, and if mentally exhausted, the recovery time will be disproportionally long. Mental fatigue after traumatic brain injury correlates with brain information processing speed. Information processing is energy consuming and requires wide-spread and specific neural signaling. Glutamate signaling is essential for information processing, including learning and memory. Low levels and the fine-tuning of extracellular glutamate are necessary to maintain a high precision in information processing. The astroglial cells are responsible for the fine-tuning of the glutamate transmission, but this capacity is attenuated by substances or conditions associated with neuro-inflammation in brain pathology. In this paper, we extend our previously presented hypothesis on the cellular mechanisms underlying mental fatigue suggesting a dysfunction in the astroglial support of the glutamate transmission. Changes in other neurotransmitters such as dopamine, serotonin, norepinephrine and acetylcholine after brain injury are also taken into consideration.